Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 62423 species occurrences available in GBIF matching the query: { "and" : [ "Country is Belgium", "TaxonKey is one of (Aponogeton distachyos L.f., Cabomba caroliniana A.Gray, Cherax destructor Clark, 1936, Crassula helmsii (Kirk) Cockayne, Egeria densa Planch., Erythranthe guttata (DC.) G.L.Nesom, Faxonius immunis (Hagen, 1870), Faxonius juvenilis (Hagen, 1870), Faxonius rusticus (Girard, 1852), Faxonius virilis (Hagen, 1870), Heracleum mantegazzianum Sommier & Levier, Heracleum persicum Desf., Heracleum sosnowskyi Manden., Houttuynia cordata Thunb., Hydrocotyle ranunculoides L.f., Impatiens glandulifera Royle, Koenigia polystachya (Wall. ex Meisn.) T.M.Schust. & Reveal, Lagarosiphon major (Ridl.) Moss, Ludwigia grandiflora (Michx.) Greuter & Burdet, Ludwigia peploides (Kunth) P.H.Raven, Lysichiton americanus Hultén & H.St.John, Myriophyllum aquaticum (Vell.) Verdc., Myriophyllum heterophyllum Michx., Petasites japonicus (Siebold & Zucc.) Maxim., Pontederia cordata L., Procambarus acutus (Girard, 1852), Procambarus clarkii (Girard, 1852), Procambarus virginalis Lyko, 2017, Saururus cernuus L., Zizania latifolia (Griseb.) Stapf)", "OccurrenceStatus is Present" ] } The dataset includes 62423 records from 62 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0100769-230224095556074/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences